2018
DOI: 10.1002/2211-5463.12479
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: IFITM3 promotes hepatocellular carcinoma invasion and metastasis by regulating MMP9 through p38/MAPK signaling

Abstract: Interferon‐induced transmembrane protein 3 (IFITM3) has been shown to be overexpressed in multiple cancers. However, the role of IFITM3 in metastasis of hepatocellular carcinoma (HCC) is still poorly understood. In this study, we showed that IFITM3 was frequently overexpressed in HCC tissues compared with adjacent nontumor tissues. Overexpression of IFITM3 was significantly correlated with tumor metastasis and poor prognosis in HCC. Knockdown of IFITM3 dramatically decreased MMP9 expression and inhibited the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 31 publications
(50 reference statements)
4
52
0
1
Order By: Relevance
“…To examine the detailed mechanisms underlying M2 macrophages' role in regulating HCC cells invasion and migration, we tested the expression of proteins that have been connected with cancer cell invasion and migration [12][13][14][15][16][17][18] in both culture alone and in co-culture. The exploratory experiments led to the focus on MMP9 as the results showed that MMP9 protein expression was increased after co-culture, both in SK-HEP-1 and HA22T HCC cells ( Fig.…”
Section: Mechanism Dissection Of How M2 Macrophages Increase the Hcc mentioning
confidence: 99%
“…To examine the detailed mechanisms underlying M2 macrophages' role in regulating HCC cells invasion and migration, we tested the expression of proteins that have been connected with cancer cell invasion and migration [12][13][14][15][16][17][18] in both culture alone and in co-culture. The exploratory experiments led to the focus on MMP9 as the results showed that MMP9 protein expression was increased after co-culture, both in SK-HEP-1 and HA22T HCC cells ( Fig.…”
Section: Mechanism Dissection Of How M2 Macrophages Increase the Hcc mentioning
confidence: 99%
“…Lue et al described how MAPK is upregulated by heparin-binding epidermal growth factor (HB-EGF)-mediated signaling, in which the HB-EGF is cut from the PCa surface by the zinc transporter, ZIP6 (LIV-1), which stimulates matrix metalloproteinase (MMP)-2/9 upregulation in other PCa cells [11]. Interferon (INF)-induced transmembrane protein 3 (IFITM3), a highly expressed transmembrane protein in cancer cells, is believed to be associated with metastasis in various cancers, e.g., acute myeloid leukemia, hepatomas, and gliomas [12][13][14][15]. In PCa, IFITM3 promotes fibroblast growth factor (FGF) expression and promotes TGF-β production, which elicits the EMT in neighboring cells in a paracrine manner [16].…”
Section: Tgf-β/mapk-mediated Emtmentioning
confidence: 99%
“…In our previous study, we found that MMP-2/-9 play important roles in the invasion of cancer cells [3]. In gastric cancer, MMP-2/-9 are over-expressed and closely correlated with the metastasis of patients [24]. In a previous study, oxymatrine has observed to inhibit the invasion of gallbladder cancer cells via inhibiting the expression of MMP-2/-9 [18].…”
Section: Discussionmentioning
confidence: 91%
“…MMPs, especially MMP-2/-9, play important roles in breaking down the ECM [22,23]. Loss of the extracellular matrix (ECM) of blood or lymph vessels allows cancer cells to invade into the blood or lymphatic system and spread to other tissues and organs [3,24]. In our previous study, we found that MMP-2/-9 play important roles in the invasion of cancer cells [3].…”
Section: Discussionmentioning
confidence: 99%